Using a quick timed‐up‐and‐go test to predict surgical risk - Catherine L. Boereboom; Rachel B. McGuinness; Philip J. J. Herrod; James E. M. Blackwell; Tanvir S. Sian; Hannah Boyd‐Carson; John P. Williams; Jonathan N. Lund; Bethan E. Phillips (Wiley, 2021)
Abstract Background Cardiorespiratory fitness (CRF) has important implications for post‐operative recovery. The timed‐up‐and‐go (TUG) test is a cheap and simple method to assess a patient's functional performance; although how well TUG correlates with results of a cardiopulmonary exercise test (CPET), the gold standard measure of CRF is unknown. Therefore, the aim of this study was to assess the correlation between CPET‐derived parameters of CRF and TUG times in a group of older adults. Methods Ninety‐eight independent community dwelling older adults [mean age: 72 years (range: 61-86), mean body mass index: 26.3 ± 3.1 kg/m2, 54 male] were recruited to this study; completing 180 CPET and TUG testing sessions over a 28 month period. The correlation between CPET‐derived CRF parameters and TUG time was assessed, and receiver operating characteristic curve analysis was performed to determine clinically useful cut‐off points in TUG time. Results Median TUG time was 7.1 s [interquartile range (IQR): 4-8.5], median VO2 peak was 24.4 mL/kg/min (IQR: 20.2-29.2), and the median anaerobic threshold (AT) was 13.4 mL/kg/min (IQR: 8.6-16.5). There was a statistically significant negative correlation between TUG time and AT (r = −0.317, P = <0.0001) and TUG time and VO2 peak (r = −0.4247, P < 0.0001). Receiver operating characteristic curve analysis determined a TUG time of ≥6.5 s to have an 82% sensitivity and 60% specificity to detect an AT <11.0 mL/kg/min, the point at below which perioperative mortality is known to increase. Conclusions Despite strong evidence for the utility of pre‐operative CPET in stratifying surgical risk, CPET is not universally available. Our finding of a correlation between TUG time and CPET‐derived parameters of CRF (AT/VO2 peak) suggests that TUG may be a useful surrogate in the pre‐operative setting.